The fronteirizo dialect of Uruguay: - Judd, Michael T. (Revista Espaço Acadêmico, 2021)
Uruguay, one of the smallest countries in all of South America, was previously believed to be a monolingual country. But when linguists began to study and describe the Spanish there around the middle of the last century, they became aware of significant linguistic hybridization which had developed all along the northern border with Brazil. A shift in linguistic dominance from Portuguese to Spanish took place only after the independence of Uruguay due to the establishment of settlements along the border, giving rise to the peculiar border speech commonly identified today as either portuñol, fronterizo, or DPU (dialectos portugueses del Uruguay).